Service science,management and engineering theory and applications - Xiong, Gang (Intelligent systems series, 2012)
The Intelligent Systems Series comprises titles that present state of the art knowledge and the latest advances in intelligent systems. Its scope includes theoretical studies, design methods, and real-world implementations and applications. Service Science, Management, and Engineering presents the latest issues and development in service science. Both theory and applications issues are covered in this book, which integrates a variety of disciplines, including engineering, management, and information systems. These topics are each related to service science from various perspectives, and the book is supported throughout by applications and case studies that showcase best practice and provide insight and guidelines to assist in building successful service systems. Presents the latest research on service science, management and engineering, from both theory and applications perspectives Includes coverage of applications in high-growth sectors, along with real-world frameworks and design techniques Applications and case studies showcase best practices and provide insights and guidelines to those building and managing service systems.